Pariwisata Dan Pelacuran Anak: Sebuah Input Bagi Pengambil Kebijakan - Elsera, Marisa (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
Tourism and prostitution like ants and sugar, as inseparable. Where there is a growing tourism destination, there helped grow prostitution. Prostitution is happening in the area of tourism destinations often do not grow with the unintended, but also grow naturally. These days, children and young women prostituted in Indonesia are increasingly being published. Young women trapped in prostitution is growing like mushrooms in the rainy season. Riau Islands Province (Riau) as one of the provinces which become the leading tourist destinations in Indonesia also inseparable from the phenomenon of prostitution. Causes of child prostitution in Riau diverse, ranging from geographic location Kepri near neighboring countries, Riau Islands as a tourist destination, economic pressure, entangled syndicates pimp, child prostitution orientation shifted into the temptation of fun and luxury. Pleasure (fun), meaning they are prostituting themselves not for economic reasons but rather to want to have fun. This occurs due to the interpretation of children and adolescents who deviate (from the morals and values of society Indonesia) towards virginity and illicit sexual relations. Then, some are prostituting themselves because of the temptation for luxury and life style.